Analysis Of Non-Financial Determinants Of Company Value In Manufacturing Companies In Indonesia - Dwi Asih Surjandari; Dewi Anggraeni; Deby Pratiwi Arlita; Riris Marintan Purba (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This study aims to investigate the nonfinancial determinants of Firm Value of manufacturing firms listed in the Indonesia Stock Exchange year 2013 up to 2017 period. The determinants represented by Good Corporate Governance (GCG), Firm Size, Dividend, Inflation Rate, Exchange Rate and Corporate Social Responsibility (CSR). The sampling method used purposive sampling and the analysis used Eviews 9.0 version. The study result shows that only one variable significantly affects Firm Value which is Institutional Ownership as proxied of GCG and the rest variables that are Independent Board another proxied of GCG, Firm Size, Dividend, Inflation Rate, Exchange Rate, and CSR does not significantly affect the Firm Value. All independent variables significantly affect Firm Value weakly simultaneously. This study implies that in formulating firm improvement performance strategy, a manufacturing firm is suggested to consider nonfinancial determinants of firm value that is Good Corporate Governance (GCG), Firm Size, Dividend, Inflation Rate, Exchange Rate and Corporate Social Responsibility (CSR).